Pre-service teacher's ability in solving mathematics problems viewed from Self-Resilience - Dede Salim Nahdi; Mohamad Gilar Jatisunda; Vici Suciawati (Malikussaleh Journal of Mathematics Learning (MJML), 2021)
The problem-solving ability is still a big problem for students. Many studies show that Indonesian students are still low in solving math problems. One thing that is needed in solving problems is self-resilience, so that students have resilience in facing problems. This study aims to analyze the differences in problem-solving abilities of pre-service elementary school teacher in terms of self-resilience. This study used a Quasi-Experiment method with the type Nonequivalent Pretest-Posttest Control Group. The population of this study were all elementary school teacher candidates at Majalengka University with a sample of 60 respondent. This study resulted in a significant difference in the increase in problem-solving abilities of student-teacher candidates. Based on Self Resilience, the group of students who received Problem Based Learning had higher problem-solving abilities than the group of students who received expository learning. Mathematical problem-solving ability requires students to have self-resilience because in solving problems, a person needs to have confidence in his ability to face problems.